2004
DOI: 10.1007/bf03192594
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal faecal excretion, gut fill, liquid and particle marker retention in mouflonOvis ammon musimon, and a comparison with roe deerCapreolus capreolus

Abstract: Seasonal faecal excretion, gut fill, liquid and particle marker retention in mouflon ovis ammon musimon, and a comparison with roe deer capreolus capreolus Seasonal faecal excretion, gut fill, liquid and particle marker retention in mouflon ovis ammon musimon, and a comparison with roe deer capreolus capreolus AbstractFive mouflon (average body mass [BM] 33 kg) and two roe deer (average BM 20 kg) with rumen cannulas were kept in large enclosures under semi-natural conditions and were used for seasonal studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Optimal digestion theory (Sibly 1981) predicts that animals adapted to a forage that yields energy and nutrients quickly would have short retention times, and those that ingest a forage that yields energy and nutrients more slowly would have longer retention times. This has been postulated for ruminants (Hanley 1982;Kay 1987a;Hofmann 1989;Clauss and Lechner-Doll 2001;Behrend et al 2004;Hummel et al 2005); however, a comprehensive dataset based on comparable measurements is still lacking.…”
Section: Predictionsmentioning
confidence: 95%
See 3 more Smart Citations
“…Optimal digestion theory (Sibly 1981) predicts that animals adapted to a forage that yields energy and nutrients quickly would have short retention times, and those that ingest a forage that yields energy and nutrients more slowly would have longer retention times. This has been postulated for ruminants (Hanley 1982;Kay 1987a;Hofmann 1989;Clauss and Lechner-Doll 2001;Behrend et al 2004;Hummel et al 2005); however, a comprehensive dataset based on comparable measurements is still lacking.…”
Section: Predictionsmentioning
confidence: 95%
“…GR have a more diverse protozoal fauna, whereas BR protozoa are mostly Entodinium sp. ; as these are particularly fast-growing ciliates, it has been suggested that other protozoa cannot establish viable populations in the reticulorumen (RR) of BR (Prins et al 1984;Dehority 1995;Dehority et al 1999;Clauss and Lechner-Doll 2001;Dehority and Odenyo 2003;Behrend et al 2004). Other parameters indicative of shorter ingesta retention times (Clauss and Lechner-Doll 2001; Behrend et al 2004) are a lower degree of unsaturated fatty acid hydrogenation in the RR, a greater number of glucose transporters, and a higher amylase activity in the small intestine of BR, 3 as well as larger faecal particles in BR.…”
Section: Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Faecal samples from zoo 151 animals were collected at particular intervals (see below for details), dried at 103 °C and 152 ground through a 1 mm sieve. Marker concentration was measured after wet ashing, 153 according to Behrend et al (2004) In other words, a slope of one and an intercept of zero were statistically not excluded in either 169 case, indicating no systematic difference between the two sampling schemes. Only data 170 calculated from all available sampling intervals are presented in the discussion.…”
Section: Mean Retention Time 146mentioning
confidence: 99%